2021
DOI: 10.3390/jcm11010205
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Trabecular Bone, Cortical Bone and Hyaline Cartilage as Well as Disturbances in Bone Metabolism and Mineralization in an Animal Model of Secondary Osteoporosis in Clostridium perfringens Infection

Abstract: There is no information regarding whether changes in the microbiological balance of the gastrointestinal tract as a result of an infection with Clostridium perfringens influence the development of metabolic bone disorders. The experiment was carried out on male broiler chickens divided into two groups: control (n = 10) and experimental (n = 10). The experimental animals were infected with Clostridium perfringens between 17 and 20 days of age. The animals were euthanized at 42 days of age. The structural parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…The higher cortical porosity in control birds indicated the higher activity of osteoblasts laying down more type I collagen which is supposed to be mineralized later ( Whitehead 2004 ). Tomczyk-Warunek et al (2021) observed a similar result where the nonchallenged control birds have a higher level of mature collagen fibers deposited in cortical bone compared to that of birds challenged with C. perfringens . In the current study, Eimeria challenge reduced BV and BS in cortical bones, indicating that smaller cortical bones compared to the nonchallenged control; these considerably affected other porosity parameters including NCP, VOP, TVP, and PP.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The higher cortical porosity in control birds indicated the higher activity of osteoblasts laying down more type I collagen which is supposed to be mineralized later ( Whitehead 2004 ). Tomczyk-Warunek et al (2021) observed a similar result where the nonchallenged control birds have a higher level of mature collagen fibers deposited in cortical bone compared to that of birds challenged with C. perfringens . In the current study, Eimeria challenge reduced BV and BS in cortical bones, indicating that smaller cortical bones compared to the nonchallenged control; these considerably affected other porosity parameters including NCP, VOP, TVP, and PP.…”
Section: Discussionmentioning
confidence: 53%
“…They observed a decrease in trabecular BV/TV, BSA, BMD, Tb.N., and Conn.D and described it as a result of a high turnover rate of trabecular bone resorption rather than trabecular bone formation due to hyperactivity of osteoclast cells and our results with the TRAP staining coincide with this mechanism. In contrast, Tomczyk-Warunek et al (2021) observed an opposite effect on the trabecular histomorphometry when broilers were challenged with C. perfringens ; they observed an increase in BV/TV, Tb.N., and Tb.Th. The increase in Tb.N.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Hence, scientists have been motivated to create hierarchical structures with multimodal porosities in one single solid body by developing new synthesis approaches [183]. Hence, it is important to consider factors such as pore type and others while designing scaffolds or implants is critical for tissue such as bone, where the structure changes significantly from the cancellous part to the cortical region [184].…”
Section: Morphology and Porositymentioning
confidence: 99%